Blockchain for and in logistics: What to adopt and where to start - Mario Dobrovnik; David Herold; Elmar Wilhelm M. Fürst; Sebastian Kummer (Logistics, 2018)
Despite the claim that blockchain will revolutionise business and redefine logistics, existing research so far is limited concerning frameworks that categorise blockchain application potentials and their implications. In particular, academic literature in transport and logistics to date has not sufficiently distinguished between blockchain adoption ('what to adopt') and the identification of the right business opportunity ('where to start'). In response, this paper (1) uses Rogers' (2003) 'attributes of innovation framework' to identify potential blockchain applications and (2) presents a framework explicating four transformation phases to subsequently categorise the identified areas of application according to their effects on organisational structures and processes. Using academic and practitioner literature, we classify possible applications for adoption and provide a framework to identify blockchain opportunities in the logistics industry, thereby helping managers to systematically assess where to start building organisational capabilities in order to successfully adopt and deploy blockchain-based technology.
Keywords: 650; blockchain; supply chain management; logistics; innovation; innovation framework; transformation